2018
DOI: 10.1007/s11103-018-0767-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis versus degradation: directions of amino acid metabolism during Arabidopsis abiotic stress response

Abstract: During abiotic stress low abundant amino acids are not synthesized but they accumulate due to increased protein turnover under conditions inducing carbohydrate starvation (dehydration, salt stress, darkness) and are degraded. Metabolic adaptation is crucial for abiotic stress resistance in plants, and accumulation of specific amino acids as well as secondary metabolites derived from amino acid metabolism has been implicated in increased tolerance to adverse environmental conditions. The role of proline, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
170
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(204 citation statements)
references
References 66 publications
14
170
0
Order By: Relevance
“…It seems to suggest that G. lemaneiformis could absorb exogenous N to produce Gln soon after the recovery of N. Asn and Gln contents were slightly increased after fourth hour of N deficiency, but they were still extremely significantly lower than that of control. This result indicated that Asn and Gln contents were synthesized at a very low level during N stress, although they could act as precursors for secondary metabolites, compatible osmolytes, or storage forms of organic N (Hildebrandt ). Given that different amino acids were decreased or increased at different time points, it means that their metabolism is somehow complicated during the N pressure period.…”
Section: Discussionmentioning
confidence: 99%
“…It seems to suggest that G. lemaneiformis could absorb exogenous N to produce Gln soon after the recovery of N. Asn and Gln contents were slightly increased after fourth hour of N deficiency, but they were still extremely significantly lower than that of control. This result indicated that Asn and Gln contents were synthesized at a very low level during N stress, although they could act as precursors for secondary metabolites, compatible osmolytes, or storage forms of organic N (Hildebrandt ). Given that different amino acids were decreased or increased at different time points, it means that their metabolism is somehow complicated during the N pressure period.…”
Section: Discussionmentioning
confidence: 99%
“…An exception might be those amino acids that serve as precursors for secondary metabolites such as the aromatic amino acids (Tzin and Galili 2010). The sum of all amino acids dropped by 29 % during stress most likely due to their use as alternative respiratory substrates and precursors for secondary metabolites (Araujo et al 2011; Hildebrandt 2018). In order to develop an idea about how long plants would be able to keep up their regular mitochondrial respiration rate when using exclusively the amino acids released by protein degradation as substrates we calculated the total number of electrons that would be transferred to oxygen via the mitochondrial respiratory chain during complete oxidation of the specific set of amino acids released during drought stress (Supp.…”
Section: Discussionmentioning
confidence: 99%
“…Proteostasis is closely connected to amino acid homeostasis since protein synthesis requires sufficient supply of loaded t-RNAs whereas proteolysis releases free amino acids. The effect of protein metabolism on the relative contents of free amino acids can be substantial in particular for low abundant amino acids such as the sulfur containing, aromatic, and branched chain amino acids (Hildebrandt 2018). In yeast and animal cells proteasome inhibition leads to cell death, which is primarily caused not by the accumulation of misfolded proteins but by a detrimental deficiency in free amino acids (Suraweera et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in contrast to most other TCA cycle intermediates, 2-oxoglutarate levels are not increased in phy mutants according to our LC-MS measurements, indicating that it may be increasingly used for the synthesis of these amino acids. The proline, serine and glutamine synthesis branch is connected to carbohydrate metabolism via short pathways and so their regulation is less energetically costly than other amino acids where synthesis and degradation requires multiple reaction steps (Hildebrandt 2018).…”
Section: Phytochrome Suppresses Stress Metabolite Synthesis In Coopermentioning
confidence: 99%
“…Proline and raffinose accumulation typically occurs in abiotic stress conditions, such as cold stress, high salinity and drought (Kaplan et al 2004;Urano et al 2009;Kempa et al 2008;Pagter et al 2017). Synthesis of glutamine from glutamate is key for nitrogen assimilation into organic molecules and high nitrogen assimilation rates are predicted to occur during cold stress (Hildebrandt 2018). Thus, phy depletion appears to elicit features of an abiotic stress response.…”
Section: Phytochrome Suppresses Stress Metabolite Synthesis In Coopermentioning
confidence: 99%